Antisepsis, disinfection, and sterilization : types, action, and resistance - McDonnell, Gerald E. (Monograph, ASM Press., 2017)
Antisepsis, Disinfection, and Sterilization: Types, Action, and Resistance by Gerald E. McDonnell is a detailed and accessible presentation of microbial control methods. Each major category, such as physical disinfection methods, is given a chapter, in which theory, spectrum of activity, advantages, disadvantages, and modes of action of the methods are thoroughly and clearly presented. Sufficient background on the life cycles and general anatomy of microorganisms is provided so that the reader who is new to microbiology will better appreciate how physical and chemical biocides work their magic on microbes. Topics covered include: Evaluating the efficacy of chemical antiseptics and disinfectants, and of physical methods of microbial control and sterlization; how to choose the proper biocidal product and process for specific applications; classic physical and chemical disinfection methods, such as heat, cold, non-ionizing radiation, acids, oxidizing agents, and metals; chemical sterlization methods that use ethylene oxide, formaldehyde, or a variety of other oxidizing agents; Modes of action of biocides in controlling microbial growth and disrupting microbial physiology; Mechanisms that microorganisms use to resist the effects of biocides. The second edition of Antisepsis, Disinfection, and Sterlization: Types, action, and resistance is well suited as a textbook and is outstanding as a reference book for facilities managers and application engineers in manufacturing plants, hospitals, and food production facilities. It is also essential for public health officials, health care professionals, and infection control practitioners. -- from back cover.